Religion and Politics over a Career. (1st November 2019) - Maddox, Marion
Abstract : A career-long focus on the intersections between religion and politicsgrew out of family, personal and academic interests. These influencesand academic explorations led to questioning the common assumptionthat religion and politics should-or even can-be 'kept separate'. On theother hand, the ways in which religion and politics intersect and interact, and their various configurations, provide fertile ground for analysis, and have important consequences for our national life. These intersectionsand interactions take distinctive forms in Australia, meaning thatwe need local research that, while informed by international models, isfirmly grounded in our own situation.